Role of Logistics in Dairy Industry - Kulkarni, Sunil (Indian Journal of Marketing, 2004)
Women constitute half the population of the world. But in many parts of the world, they seem to be underpowered. Relative to men, they are relegated to secondary position, be it in the household, society in general, and workplace or in governance. It is this perceived gender inequality and the urge to remove it and 'empower' women that have constituted the motive force for the formation of Self Help Groups (SHGs). Self Help Group can be defined as a 'Voluntary Association' of the poor with a common goal of social and economic empowerment. The purpose behind the formation of Self-Help Groups may be to pool in the resources of members to meet their needs. Groups should be homogenous and democratically functioning. The habit of thrift and contributing to common funds mobilized to mitigate the urgent needs of the members and ensuring prompt recovery is required for better functioning of (SHGs).